Tracheostomy decannulation protocol in a tertiary pediatric hospital - Tiago Chantre; Inês Alpoim Moreira; Mafalda Barroso; Mariana Oliveira; Herédio Sousa (Revista Portuguesa Otorrinolaringologia e Cirurgia de Cabeça e Pescoço)
Introduction - Pediatric tracheostomy is associated with significant morbidity, with decannulation being the primary outcome, as soon as the underlying indication for the procedure is resolved. There is great variability in pediatric decannulation protocols, making it imperative to create a protocol that reflects the reality of Portuguese hospitals.